1995
DOI: 10.1111/j.2042-3306.1995.tb04970.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise performance indices in normal and anabolic steroid treated trotters

Abstract: SummarySix adult Finnhorse trotters performed a standardised exercise test (SET) on a treadmill and a 4000 m maximal exercise test (MET) on a racetrack before, immediately and 13 weeks after a 14 week treatment with nandrolone laurate. Six other trotters served as contrculs. All horses were trained during the whole experiment. Blood lactate concentration, VZo0, VLa4 and red cell volume (CV) were determined in connection to the SET and blood lactate concentration, heart rate and performance time in the MET. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
0
17
2
Order By: Relevance
“…The short nandrolone treatment used here did not increase CV, thus oxygen-carrying capacity remained unaffected. This ®nding differs from an earlier study, in which Hyyppa È et al (1995) reported a signi®cant increase in CV after 14-week nandrolone treatment, although equal plasma nandrolone concentrations were achieved. This suggests that long treatments with anabolic steroids are needed before erythropoiesis is increased.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The short nandrolone treatment used here did not increase CV, thus oxygen-carrying capacity remained unaffected. This ®nding differs from an earlier study, in which Hyyppa È et al (1995) reported a signi®cant increase in CV after 14-week nandrolone treatment, although equal plasma nandrolone concentrations were achieved. This suggests that long treatments with anabolic steroids are needed before erythropoiesis is increased.…”
contrasting
confidence: 99%
“…In mares and geldings, a 14‐week treatment with nandrolone laurate increases red cell volume, makes the horses more aggressive, and increases the percentage of type IIA fibres and the cross‐sectional area of type I fibres (Hyyppä et al., 1995; Hyyppä et al., 1997a). Despite these behavioural and other changes, no controlled studies on horses yet exist to show whether anabolic steroids improve physical performance in comparison with that of similarly trained control horses, and at least three studies demonstrate that anabolic steroids offer no beneficial effect on exercise performance (Snow et al., 1982; Thornton et al., 1991; Hyyppä et al., 1995). Alway and Starkweather (1993) have suggested that anabolic steroids may improve adaptation to physical exercise, and therefore enhance the ability of an individual to tolerate increased intensity of training more than would otherwise be possible.…”
Section: Introductionmentioning
confidence: 99%
“…3). In the AS group, but not in the C group, the AR concentration at the end of nandrolone treatment correlated positively with percentage of type IIA fibres (r =0.933, P < 0.05; fibre type values taken from HyyppA et al, 1995).…”
Section: Cballgrs In the N/{ijdr Compositianmentioning
confidence: 79%
“…Androgenic, anabolic steroids (AS), synthetic derivatives of testosterone, have been widely used to improve physical performance, although this is scientifically controversial (CELOTfl and NEGRI CBSI, 1992;SNOW, 1993). In controlledstudies, administration of AS to horses has failed to improve performance capacity (SNOW et al, 1982b;THORNTON et al, 1991;HyyppA et al, 1995), whereas other anabolic effects have been observed, such as increases in erythropoiesis and nitrogen retention (SNOW et al, 1982b;NIMMO et al, 1982;HyyppA et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the well‐documented advantages that anabolic steroids offer to human athletes, the effects of anabolic steroids in equine competitors are not well‐established . A study has shown that short‐term nandrolone (17β‐hydroxyestr‐4‐en‐3‐one) administration increased the glycogen content of post‐exercise muscle tissue; however, this is in contrast with two studies that found no observable changes resulting from nandrolone administration . It has been shown that steroid administration delayed closure of epiphyseal growth plates in Standardbreds, and suggested that this could lead to a potential increase to the long‐term risks of injury during training .…”
Section: Anabolic Steroids In Equine Sportsmentioning
confidence: 99%